Support for Coteaching in Clinical Practice: The Development and Use of a Coassessing Rubric for Collaboratively Analyzing Student Learning. Issue 1 (3rd April 2022) - Guise, Megan; Hegg, Sarah; Hoellwarth, Chance; O'Shea, Mark
ABSTRACT: Coteaching, an alternative to traditional conceptions of student teaching in general teacher preparation, may be enhanced if researchers and practitioners achieve consensus with respect to operational definitions and descriptions of practice. The focus of this article is coassessing – one component of coteaching – where coteachers collaboratively analyze the results of student assessments and determine instructional next steps. Through a review of coassessing literature and analyses of coassessing videos, we developed a coassessing rubric to support coassessing implementation. We describe the methods used to develop the coassessing rubric and outline the use of the rubric as a resource for advancing coassessing practice.